Let
x--------> the cost of the larger fish
y--------> the cost of the smaller fish
we know that
-------> equation A
-------> equation B
Step 1
<u>Solve the system of linear equations</u>
Substitute equation B in equation A
![3y+y=\$3,952](https://tex.z-dn.net/?f=3y%2By%3D%5C%243%2C952)
![4y=\$3,952](https://tex.z-dn.net/?f=4y%3D%5C%243%2C952)
![y=\$3,952/4](https://tex.z-dn.net/?f=y%3D%5C%243%2C952%2F4)
![y=\$988](https://tex.z-dn.net/?f=y%3D%5C%24988)
<u>Find the value of x</u>
![x=3*988=\$2,964](https://tex.z-dn.net/?f=x%3D3%2A988%3D%5C%242%2C964)
Step 2
<u>Find the weigh of each fish</u>
we know that
the rate is ![13\frac{\$}{pound}](https://tex.z-dn.net/?f=13%5Cfrac%7B%5C%24%7D%7Bpound%7D)
To obtain the weigh of the fish divide the cost of the fish by the rate
<u>Larger fish</u>
<u>
</u>
<u>Smaller fish</u>
<u>
</u>
therefore
<u>the answer is</u>
The weigh of the larger fish was <u>
</u>
The weigh of the smallerr fish was <u>
</u>